2008
DOI: 10.1089/pho.2007.2060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CO2Laser on the Permeability of Dentinal Tubules: A Preliminaryin VitroStudy

Abstract: The 9.6-microm CO(2) laser appears to be a promising tool in the clinical setting. However, further investigation is needed to ensure maximum effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The particular properties of each type of laser and the specific target tissue make them suitable for different procedures (Alfredo et al, 2008;Nakamura et al, 2006;Santos et al, 2005;Slutzky-Goldberg et al, 2008;). The CO 2 laser energy is conducted thought a hollow wave-guide and the wavelength of 10.6 lm places it at the end of the mid-infrared invisible portion of the light spectrum (Coluzzi, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular properties of each type of laser and the specific target tissue make them suitable for different procedures (Alfredo et al, 2008;Nakamura et al, 2006;Santos et al, 2005;Slutzky-Goldberg et al, 2008;). The CO 2 laser energy is conducted thought a hollow wave-guide and the wavelength of 10.6 lm places it at the end of the mid-infrared invisible portion of the light spectrum (Coluzzi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits of CO 2 laser in endodontic field have also been investigated, and studies have demonstrated that this laser can be used to alter dentine surface of root canal walls as well as dentine permeability (Slutzky-Goldberg et al, 2008), pulpotomy, apicectomy (Stabholz et al, 2004), closure of apical foramina (Moritz et al, 1997), disinfection of infected root canals (Le Goff et al, 1999), and cleaning and shaping the root canal system (Stabholz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…22 Melting of dentin can seal the dentinal tubules and alleviate pain in cases of dentinal hypersensitivity. 23 Read et al 24 reported that the use of lasers may enhance the success of endodontic apical procedures by reducing leakage because it can result in a surface less permeable to fluids. The ultra-structural changes of the surface are followed by chemical modifications.…”
Section: Discussionmentioning
confidence: 99%